2014
DOI: 10.1364/oe.22.015737
|View full text |Cite
|
Sign up to set email alerts
|

Accurate vectorial finite element mode solver for magneto-optic and anisotropic waveguides

Abstract: In this work, a dielectric waveguide mode solver is presented considering a general nonreciprocal permittivity tensor. The proposed method allows us to investigate important cases of practical interest in the field of integrated optics, such as magneto-optical isolators and anisotropic waveguides. Unlike the earlier developed mode solver, our approach allows for the precise computation of both forward and backward propagating modes in the nonreciprocal case, ensuring high accuracy and computational efficiency.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 66 publications
(102 reference statements)
0
18
0
Order By: Relevance
“…Thirdly, the mode set (ψ ψ ψ 2d ) of the adjoint system is selected as the countering propagating modes of the original system (φ φ φ 2d ). As such, the total degree of freedom of unknows is halved [30]. We note that GCMT can also be applied to bianisotropic waveguides [33].…”
Section: [E E E(r R R) H H H(r R R)] T Where E E E(r R R) = E E E(mentioning
confidence: 96%
See 2 more Smart Citations
“…Thirdly, the mode set (ψ ψ ψ 2d ) of the adjoint system is selected as the countering propagating modes of the original system (φ φ φ 2d ). As such, the total degree of freedom of unknows is halved [30]. We note that GCMT can also be applied to bianisotropic waveguides [33].…”
Section: [E E E(r R R) H H H(r R R)] T Where E E E(r R R) = E E E(mentioning
confidence: 96%
“…The particular choice of the mode sets [28][29][30][31] is relevant: (1) it is necessary to get a functional of coupled modes that is independent of z, meaning the terms e ±iβ z in the inner-product between the modes sets φ φ φ and ψ ψ ψ are canceled; (2) the mode pair of counter-propagating modes has a definite relation, hence φ φ φ can be deduced from ψ ψ ψ, and vice versa. It is easy to get the z-independent and source-free wave-equation for the mode profiles φ φ φ 2d = [e e e + , h h h + ] of the original problem as follows .…”
Section: [E E E(r R R) H H H(r R R)] T Where E E E(r R R) = E E E(mentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of practical interest, B ext lies in the x-y plane of the waveguide, so ε xy =0. As a result, it can be shown that [9] ( ) ( ).…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Perfectly matched layer boundary conditions, in both coordinate systems, have been implemented to include radiation loss. Unlike the earlier developed mode solver based on the perturbation method, our approach allows for the precise computation of both forward and backward propagating modes in the nonreciprocal case, ensuring high accuracy and computational efficiency, as shown in [9]. As a result, the nonreciprocal loss/phase shift can be directly computed.…”
Section: Mathematical Modelmentioning
confidence: 99%